(untitled) (Chittagong University Journal of Biological Sciences, 2024)
The growth and mortality rates of Labeo rohitaom the Halda River strain and the hatchery strain were studied under identical water quality and environmental conditions to identify the better performer. 250 Rohu fish fries from the Halda River and the hatchery were reared for this experiment. The rearing trial was performed for 14 weeks in 12 m3 net cages, each with three replica sets in an earthen pond. Fishes were sampled weekly for measuring body weight and length. The final mean weight was significantly higher in the Halda strain (57.46 ± 22.91 g) compared to the hatchery strain (24.20 ± 7.61 g) (p < 0.05), with weight gain in the Halda strain more than twice that of the hatchery strain. In most sampling stages, the growth rate of Labeo rohita was significantly higher (p < 0.05) in the Halda strain. The final mean length was also greater in the Halda strain (13.07 ± 1.63 cm) compared to the hatchery strain (10 ± 1.08 cm). Mortality rates were lower in the Halda strain (15.60%) than that of the hatchery strain (31.20%) over the 14 weeks. These findings suggest that the Halda strain significantly outperforms the hatchery strain in growth and survival under controlled conditions. Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 83-90, 2024